Disability, medicine, and healing discourse in early Christianity: new conversations for health humanities - Holman, Susan R.; De Wet, Chris L.; Zecher, Jonathan L. (Religion, medicine and health in late antiquity, 2024)
"Using contemporary theories drawn from health humanities, this volume analyses the nature and effects of disability, medicine, and health discourse in a variety of early Christian literature. In recent years, the "medical turn" in early Christian studies has developed a robust literature around health, disability, and medicine, and the health humanities have made critical interventions in modern conversations around the aims of health and the nature of healthcare. Considering these developments, it has become clear that early Christian texts and ideas have much to offer modern conversations, and that these texts are illuminated using theoretical lenses drawn from modern medicine and public health. The chapters in this book explore different facets of early Christian engagement with medicine, either in itself or as metaphor and material for theological reflections on human impairment, restoration, and flourishing. Through its focus on late antique religious texts, the book raises questions around the social, rather than biological, aspects of illness and diminishment as a human experience, as well as the strategies by which that experience is navigated. The result is an innovative and timely intervention in the study of health and healthcare, that bridges current divides between historical studies and contemporary issues. Taken together, the book offers a prismatic conversation of perspectives on aspects of care at the heart of societal and individual "wellness" today, inviting readers to meet or revisit patristic texts as tracings across a map of embodied identity, dissonance, and corporal care. It is a fascinating resource for anyone working on ancient medicine and health, or the social worlds of early Christianity"--